Brazing TiC/Ti matrix composite using TiNi eutectic braze alloy. (October 2018) - Dong, Duo; Zhu, Dongdong; Zheng, Huixia; Wang, Gang; Xu, Haitao; Lin, Feng; He, Qin; Ni, Chengyuan
Abstract: Vacuum brazing of TiC/Ti matrix composite was performed using Ti-28mass%Ni eutectic brazing alloy. The brazed joints were obtained at different temperatures and holding times. The microstructure and mechanical properties of the joints were investigated in detail. The results show that the typical interfacial microstructure of the brazed joints is Ti solid solution, δ-Ti2 Ni phase and TiC particles. As the brazing temperature was increased from 1283 K/10min to 1353 K/10min, the joint shear strength first increased and then decreased. Prolonging the holding time, caused the shear strength of the joints to decrease. The maximum shear strength reached 711.4 MPa at 1333 K for 10 min, which is more than twice that obtained with the conventional brazing of Ti alloys. The fracture location varied from the brazing joints to the substrate in different brazing processes. The fracture path, located at the substrate, can only be found at 1333 K/10min. The microstructural evolution of the brazed joints with different brazing processes was clarified and its relationship with the mechanical performance was revealed in detail. Highlights: The maximal shear strength of the joint reached 711.4 MPa at 1333 K/10min. The microstructures of the brazed joints were Ti solid solution, δ-Ti2 Ni and TiC. The fracture path, located at the substrate, can only be found at 1333 K/10min.